Luxury fashion retail management - Choi, Tsan-Ming; Shen, Bin (Springer, 2017)
Using various research methodologies, such as reviews, case studies, analytical modeling and empirical studies, this book investigates luxury fashion retail management and provides relevant insights, which are beneficial to both industrialists and academics. Readers gain an understanding of luxury fashion retailing, including proper operations and strategic management, which now are the most crucial items on the luxury fashion industry's senior management agenda.
Keywords: Business.; Marketing.; Sales management.; elektronické knihy; electronic books